The 2015 Kogi State Gubernatorial Election and the Crisis of Political Mandate: The Failure of Party Politics? - Omodia, S.M (Advances in Social Sciences Research Journal, 2016)
This paper discusses the crisis of political mandate in the 2015 kogi state gubernatorial election with specific focus on the All Progressive Congress (APC). The paper using Almond and Verba’s conception of political culture as a framework of analysis, unfolds the poor aggregative capability of the Nigeria party system as well as the restrictive participatory political culture in the process of elite recruitment. The argument of the paper is that the current crisis of political mandate in kogi state which is associated with 2015 gubernatorial election is a function of the failure of the Nigerian party system to provide through an encompassing participatory process, shared aspiration and party ideals of political representation as a tool of crisis management at the intra-party level. The result has been party indiscipline, disloyalty and the externalization of conflicts through the over-independence on judicial interpretations and pronouncements by the courts at the expense of the electoral process. In conclusion ,the paper accentuate that if the present democratic experiment of the Nigerian fourth republic is to stand the test time, the process must be built on a functional aggregative capability of political parties that is anchored on a participant political culture.